Spreading the word: A process evaluation of a voluntary AOD prevention program. (6th April 2015) - Edelen, Maria Orlando; Tucker, Joan; D'Amico, Elizabeth
<x xml:space="preserve">Abstract</x> Background and Objectives Research on voluntary after‐school alcohol and other drug (AOD) prevention programs is limited. It is important to increase understanding of students' motivation to attend these types of programs and their tendency to transfer program information to peers. This paper summarizes efforts to evaluate process information for CHOICE, a voluntary after‐school AOD prevention program for middle‐school youth. Methods A survey administered to 1899 students aged 10–16 in seven schools assessed: (1) why students choose to attend CHOICE (2) barriers to attendance; and (3) how program information is disseminated to non‐participants. Frequencies of responses from participants and non‐participants were compared. Results Participants were motivated by several features, most notably, the demeanor of the group leaders and enjoyable curriculum content. Barriers to attendance were primarily logistic, but results also suggest that the promotion message should more effectively emphasize that CHOICE is appropriate for everyone. The majority of students knew about CHOICE, both through advertising and conversations with friends. Non‐participants' detailed reports of what they heard from friends corresponded closely with what participants reported sharing. Discussion and Conclusions The use of dynamic group leaders is critical to engaging students in voluntary programs. Offering the program on different days of the week or at different times (eg, before school) may improve attendance rates. Peer networks represent a critical pathway for prevention information that can help increase program impact. Scientific Significance These results can be used to inform modifications to existing voluntary after‐school AOD prevention programs to obtain higher attendance rates and more widespread dissemination of the intervention message. (Am J Addict 2014:XX:XX–XX).